Investigation of Learning Experiences of Primary School Students with Mathematics Learning Disability with Authentic Activities - Sanal, Seda Ozer (My University, 2023)
This study aimed to examine the primary school children learning experiences with mathematics learning difficulties in authentic contexts. Eight primary school students with mathematics difficulties participated in the research as multiple case studies. Research data were obtained with three different data collection methods. These were determined as semi-structured interviews (before and after observation), in-class observation and document review. At the end, as the result of the data collection process, which lasted for a total of five months, the students’ opinions showed that; Mathematics teaching supported by authentic activities brought along features such as familiar problems, well-defined tasks, cognitive support, authentic assessment and reflection. In addition, it was seen from the student data who participated in all of the authentic tasks that; Students who participated in authentic tasks with their peers, teachers, or parents had higher completion rates.
Keywords: Case study; primary school student; constructivism; Math learning disability; authentic context